Discovery Learning Model on Improving Social Studies Learning Outcomes at Primary School - Intan Sari Kowarin; Nathalia Yohana Johannes; Leonid Ritiauw (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Social Studies (IPS) learning is often passive and teacher-centered, resulting in low student engagement and suboptimal learning outcomes. This study aims to examine the effect of the Discovery Learning model on improving Social Studies learning outcomes in fifth-grade students of Warwut Public Primary School, Maluku Province, Indonesia. The approach used was quantitative with a pre-experimental design (One-Group Pretest-Posttest Design). The research subjects included all 21 fifth-grade students, selected using a total sampling technique. Data were collected through a validated multiple-choice learning outcome test instrument (Cronbach's Alpha = 0.862) and an observation sheet. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and a paired-samples t-test using SPSS version 27. The results showed a significant increase in the average score from 65.10 in the pretest to 87.38 in the posttest, with a mean gain of 22.28 points. The normality test confirmed that both data were normally distributed (p > 0.05). The hypothesis test obtained a significance value of 0.000 (p < 0.05), so the null hypothesis was rejected. These findings confirmed that the application of Discovery Learning through six syntactic stages—stimulation, problem identification, data collection, data processing, proof, and drawing conclusions—significantly improved students' social studies learning outcomes. Practically, this study successfully transformed the conventional passive instruction pattern into active, student-centered learning. This model was proven effective in increasing student engagement, critical thinking skills, and conceptual understanding at all levels of academic ability.